1992
DOI: 10.1159/000267148
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Irrigating Solutions and Vitrectomy- Related Changes (in Protein, Lactic and Ascorbic Acid) in Rabbit Vitreous

Abstract: Vitrectomy and the subsequent vitreous fluid exchange alter the chemical and physical properties of the vitreous. This study assessed the time course alterations of total protein, ascorbic acid and lactic acid in the rabbit vitreous cavity following vitrectomy. Normal values were 2.2 ± 1.2 mg/ml, 8.5 ± 1.0 mg/l00 ml and 16.8 ± 3.5 μmol/ml, respectively. Nine groups of 5–10 adult albino rabbits underwent closed vitrectomy using physiologic saline, Ringer’s lactate and BSS plus solutions. Samples were withdrawn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…This might cause harmful retinal oedema, as previously reported by Manzanas et al, or some other type of damage to bipolar, Mueller or other inner retinal cells that contribute to the ERG b-wave. 17 Our limited histological specimens corroborate our electrophysiological findings. This study is not free of some shortcomings: First, analysing b-wave and a-wave ratio and/or recording ERG using the International Society for Clinical Electrophysiology of Vision (ISCEV) standard would have been more informative, as we used total ERG amplitude for the analysis.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This might cause harmful retinal oedema, as previously reported by Manzanas et al, or some other type of damage to bipolar, Mueller or other inner retinal cells that contribute to the ERG b-wave. 17 Our limited histological specimens corroborate our electrophysiological findings. This study is not free of some shortcomings: First, analysing b-wave and a-wave ratio and/or recording ERG using the International Society for Clinical Electrophysiology of Vision (ISCEV) standard would have been more informative, as we used total ERG amplitude for the analysis.…”
Section: Discussionsupporting
confidence: 86%
“…2 16 Manzanas et al observed that intraocular concentrations of protein increased to nearly the same extent after vitrectomy in rabbits using BSS-Plus, saline and LR without a statistical difference between each solution. 17 They also observed that lactic acid (assumed to be produced mainly by the retina) increased with saline and LR but not with BSS-Plus. Ascorbic acid was highest in the vitreous if vitrectomy was performed using saline as intraocular irrigating solution.…”
Section: Discussionmentioning
confidence: 96%
“…In our study, the development of complicated cataract after vitrectomy with silicone oil tamponade occurred in 77% of eyes on day 90 after operation, and it is consistent with the literature mentioned above. It was reported that some proteins, vitamin C, and lactic acid were found elevated in the vitreous cavity after vitrectomy, and all of them could scavenge active free radical and singlet oxygen and convert them into peroxide ions [ 26 ], indicating that the elevation of reactive oxygen species is involved in the process of complicated cataract. Studies have found that the oxidation of lens protein during vitrectomy was one of the reasons for nuclear cataract after vitrectomy [ 27 ], whereas adding antioxidants into the perfusion fluid during vitrectomy could inhibit the abnormal lens epithelial cell growth and lens fiber formation and thus prevent the cataractogenesis [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…After further technical refinements [4,5], vitrectomy has become the second most common surgery in ophthalmology now covering emergency and elective indications [3,6]. During the surgical procedures, many factors that might harm the tissue are among others the use of excessive endoillumination [7], an irrigation solution with a different composition than the human vitreous [8], the suppression of blood flow [9], air infusion [10], drugs [11] and medical devices [12]. All these elements are in direct contact with the retina and can potentially affect the neuronal tissue.…”
Section: Introductionmentioning
confidence: 99%